2021
DOI: 10.1016/j.scitotenv.2021.147463
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring waves of the COVID-19 pandemic: Inferences from WWTPs of different sizes

Abstract: Wastewater based epidemiology was employed to track the spread of SARS-CoV-2 within the sewershed areas of 10 wastewater treatment plants (WWTPs) in Catalonia, Spain. A total of 185 WWTPs inflow samples were collected over the period consisting of both the first wave (mid-March to June) and the second wave (July to November). Concentrations of SARS-CoV-2 RNA (N1 and N2 assays) were quantified in these wastewaters as well as those of Human adenoviruses (HAdV) and JC polyomavirus (JCPyV), as indicators of human … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
32
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(45 citation statements)
references
References 42 publications
5
32
1
Order By: Relevance
“…Since these excreta are frequently shed into domestic sewage, wastewater surveillance of SARS-CoV-2 RNA has emerged as a non-intrusive approach to monitor and manage coronavirus disease 2019 (COVID-19) (Bivins et al, 2020;Fuschi et al, 2021;Lundy et al, 2021). Community-level COVID-19 dynamics have been assessed (Fernandez-Cassi et al, 2021) by measuring SARS-CoV-2 RNA in both raw sewage (Agrawal et al, 2021;Li et al, 2021) and settled solids (Wolfe et al, 2021) at wastewater treatment plants (WWTPs) of varying sizes (Rusiñol et al, 2021). Monitoring wastewater from buildings has also proven useful as an approach for managing COVID-19 at finer spatial scales on college campuses (Betancourt et al, 2021;Harris-Lovett et al, 2021), in schools (Crowe et al, 2021;Hassard et al, 2021), in skilled nursing facilities (Spurbeck et al, 2021), and even on aircraft and cruise ships (Ahmed et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Since these excreta are frequently shed into domestic sewage, wastewater surveillance of SARS-CoV-2 RNA has emerged as a non-intrusive approach to monitor and manage coronavirus disease 2019 (COVID-19) (Bivins et al, 2020;Fuschi et al, 2021;Lundy et al, 2021). Community-level COVID-19 dynamics have been assessed (Fernandez-Cassi et al, 2021) by measuring SARS-CoV-2 RNA in both raw sewage (Agrawal et al, 2021;Li et al, 2021) and settled solids (Wolfe et al, 2021) at wastewater treatment plants (WWTPs) of varying sizes (Rusiñol et al, 2021). Monitoring wastewater from buildings has also proven useful as an approach for managing COVID-19 at finer spatial scales on college campuses (Betancourt et al, 2021;Harris-Lovett et al, 2021), in schools (Crowe et al, 2021;Hassard et al, 2021), in skilled nursing facilities (Spurbeck et al, 2021), and even on aircraft and cruise ships (Ahmed et al, 2020b).…”
Section: Introductionmentioning
confidence: 99%
“…Wastewater-based epidemiology (WBE) has been used in areas with centralized sewage network systems for evaluating the circulation of etiological agents of communicable diseases such as hepatitis C virus, poliovirus, and antibiotic-resistant bacteria, consumption patterns of illegal drugs, nicotine, alcohol, and pharmaceuticals in communities (Gracia-Lor et al 2017, Lorenzo and Picó 2019, Sims et al 2020. Recently, WBE has been reported as a quick, sensitive, and cost-effective approach for monitoring the prevalence, trend, and circulation of coronavirus disease pandemics at the population level (Medema et al 2020a, Hart and Halden 2020, Sherchan et al 2020, Gonzalez et al 2020, Hillary et al 2021, Rusiñol et al 2021, Lundy et al 2021, and as an early warning tool (Medema et al 2020a, Wu et al 2020a, Ahmed et al 2021a.…”
Section: Introductionmentioning
confidence: 99%
“…The use of mobile device data (Thomas et al, 2017), chemical biomarkers present in urine (e. g. caffeine, pharmaceuticals) (Rico et al, 2017) or human-specific microbial/molecular markers (e.g. crAssphage, human adenovirus (HAdV), JC polyomavirus (JCPyV)) (Rusiñol et al, 2021;Sala-Comorera et al, 2021), are alternative metrics that have been shown to reduce measurement uncertainty when used to estimate population size for normalisation of target analyte concentrations.…”
Section: Population Factorsmentioning
confidence: 99%